THE SHARIA (LEGAL) FOUNDATION OF RISK SHARING IN TAKAFUL (INSURANCE) OPERATIONS (AUN INTERNATIONAL CONFERENCE, 2025)
Takaful, the Islamic alternative to conventional insurance, is founded on the principles of mutual cooperation, responsibility, and risk sharing in accordance with Shariah (Islamic law). Unlike conventional insurance, which often involves elements of gharar (uncertainty), maisir (gambling), and riba (interest), Takaful is structured around the concepts of ta’awun (mutual assistance) and tabarru’ (donation). This article explores the Shariah foundations of risk sharing in Takaful operations, tracing historical origins, reviewing key literature, detailing methodological approaches in implementation, and offering conclusions and policy recommendations for strengthening Takaful’s global viability.